Uso unico - impacto permanente: uma revisão bibliográfica sobre os desafios da reciclagem de plásticos médicos - Barreto, Lívia Marques Santos (Universidade Federal de São Carlos, 2026)
The increasing use of plastics, particularly intensified during the COVID-19 pandemic, has led to a significant rise in the generation of healthcare waste, highlighting the need for sustainable management practices for these materials. In this context, the recycling of medical plastics faces several challenges, including the diversity of polymers used, which hinders joint recycling due to their different physicochemical properties; the risk of infection associated with contaminated waste, which requires rigorous pre-treatment procedures; pollution resulting from incineration, which releases greenhouse gases and contributes to environmental contamination; the generation of microplastics and nanoplastics, which can persist in ecosystems and be ingested and/or inhaled; the presence of potentially toxic chemical additives that may leach into the environment during waste disposal or processing; and the lack of material identification, which hinders proper segregation and compromises the efficiency of recycling processes. Given this scenario, this study aimed to critically analyze these barriers and discuss possible solutions based on a review of the scientific literature. Finally, sustainable waste management practices were addressed, including appropriate segregation strategies, recycling methods compatible with hospital and industrial settings, and approaches based on circular economy principles, aiming to reduce environmental impacts and promote safer and more efficient management of medical plastic waste.
Single use – permanent impact: a literature review on the challenges of medical plastic recycling
Keywords: Resíduos plásticos médicos; Reciclagem; Economia circular; Sustentabilidade; Gestão de resíduos hospitalares; CIENCIAS EXATAS E DA TERRA::QUIMICA; 12. Consumo e Produção Responsáveis; 9. Indústria, Inovação e Infraestrutura; 13. Ação contra a Mudança Global do Clima